Documenting the Black experience : essays on African American history, culture and identity in nonfiction films - Lawrence, Novotny, 1973- (McFarland & Company, Inc., Publishers, 2014)
"History taught at the elementary, middle, high school and even college levels often excludes significant events from African American history, such as the murder of Emmett Till or the Ku Klux Klan's murder of four black girls in the Sixteenth Street Baptist Church bombing in Birmingham which are integral parts of history"--